Examining Organic Mulch Sheet on the Growth and Yield of Shallot (Allium ascalonicum L.) - Iriany, Aniek; Lestari, Rina; Chanan, Mochammad (International Journal of Engineering and Technology, 2019)
Shallot is a vegetable commodity with a high economic value, as a source of farmers' income and foreign exchange. The National productivity of shallot in East Java continues to decrease. In the year of 2010, the production reached 9.98 tons/ha, and it declined to 9.34 tons/ha in 2013. One of the obstacles of shallot production is uncertain climate condition. Mulching is one of the efforts to control the microclimate around the plant. Organic mulch engineering into organic paper mulch is expected to overcome the above problem. The basic principle refers to the process of manufacturing synthetic paper. The research was conducted at the Experimental Farm of Faculty of Agriculture, University of Muhammadiyah Malang. The study used simple-randomized block design to test the treatment of organic material composition which consists of 6 treatments, and each treatment is repeated three times. The treatment is the basic material composition of water hyacinth plants as fine fibers, straw as rough fiber materials and leather waste as decomposing fiber material and flexibility. Observed variables include the growth and yield of shallot, climate and physical test. Each data is analyzed by F test and comparison test (Honest Significant Difference or HSD 5%). Based on comparative tests on the diameter of tuber, the number of tuber, fresh weight and dry weight it indicates that the use of organic paper mulch on treatment A where hyacinth plants: Straw: Waste Leather (5: 3: 2) and B where hyacinth plants: Straw: Waste Leather (5: 2: 3) is significantly different compared with other treatments. Increasing of fresh weight by applying organic mulch sheet and 103,73% more than non mulch and 36,84 % more than black silver plastic mulch. whereas the effect of organic paper mulch on vegetative phase of shallot is not significant.Â